If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2(c + -3) = -11 Reorder the terms: 0.2(-3 + c) = -11 (-3 * 0.2 + c * 0.2) = -11 (-0.6 + 0.2c) = -11 Solving -0.6 + 0.2c = -11 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '0.6' to each side of the equation. -0.6 + 0.6 + 0.2c = -11 + 0.6 Combine like terms: -0.6 + 0.6 = 0.0 0.0 + 0.2c = -11 + 0.6 0.2c = -11 + 0.6 Combine like terms: -11 + 0.6 = -10.4 0.2c = -10.4 Divide each side by '0.2'. c = -52 Simplifying c = -52
| -8(4n-5)= | | (x-1+2i)(x+1-2i)=0 | | 100x^(1/2)-2x=625 | | 5x-4=-4x+32 | | 9a+5b=18 | | 135=67+j | | 77=e+28 | | 4x-5x+5x-8x= | | 18=d-57 | | u/6=3 | | 10*x-6=31 | | -6(-7n-6)= | | -7y+4=-10 | | (n+5)+(4n-3)+48=180 | | 3y-4+y+42=6y+40-4y | | 3x-4+4x=16 | | y/5-2/7=y/7-2/7 | | -12t^4+28t^3+5t^2= | | 2x+16=60 | | h-52=22 | | 10*3a=31 | | 9x-4(x-3)=15x-7 | | 12m^3+3m^2+9m=0 | | 4(1)=y+3 | | (2x+6)+(3x+2)=0.5 | | 6(-8r-2)= | | 4(-1)=y+3 | | 74-b=19 | | 65=z+19 | | 3q=27 | | 3-c=14 | | 62=71-s |